Effectiveness of Cervical and Upper Shoulder Stabilization Exercises in Subjects With Rheumatoid Arthritis Patients Associated with Neck Pain - Raj Mhatre; Smita Pati (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Rheumatoid arthritis is an immunological mediated, chronic inflammatory multisystem diseasewhich involves inflammation of the peripheral joint. Ra affects about 24.5 million people as of 2015 and theincidence rate is more dominated amongst female. Historically the involvement of the cervical spine in laterstages of rheumatoid arthritis isn’t uncommon. Specifically, C1 and C2 are involved as they are the onlyvertebrae without intervertebral disc and synovial lining and hence they are very susceptible to inflammationdue to autoimmune reaction. The alteration in the range of motion is quite significant at the cervical spine.The biomechanics of the cervical spine and shoulder joint are interlinked with each other. The protocol ofspecific cervical and upper shoulder stabilization exercises with electrical modalities like hot-moist packand transcutaneous electrical nerve stimulation and short wave diathermy therapy was conducted to findout the effectiveness of scheduled, designed physiotherapy protocol of specific stabilization exercises alongwith electrotherapy for cervical spine and upper shoulder stabilization exercises to see the improvement incervical and shoulder range of motion and pain in patients with rheumatoid arthritisMethodology: An observational study was conducted in 25 patients at Karad with a study duration of 6months. The inclusion criteria were the patient with rheumatoid arthritis any age and gender willingly toparticipate. The outcome measures were universal goniometer for assessing cervical and shoulder range ofmotion, the visual analogue scale for pain assessment.Conclusion: The study concluded that there was a significant reduction in the range of motion in both thecervical spine and shoulder joint. The visual analogue scale suggests there was significant pain present inthe shoulder joint and cervical spine. Post-treatment assessment suggests the improvement in the range ofmotion and pain that leads to improvement in the quality of life.